Methods of test for sodium tripolyphosphate (pentasodium triphosphate) and sodium pyrophosphate (tetrasodium pyrophosphate) for industrial use. Condensed phosphates for industrial use (including foodstuffs). Determination of arsenic content. Silver diethyldithiocarbamate photometric method Part 12, (28th September 1979) - British Standards Institution,
No abstract available